PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP KEAKTIFAN SISWA PADA PENDIDIKAN PANCASILA KELAS 2 SEKOLAH DASAR - Utari Dwi Istichomah; Satrio Wibowo; Galuh Kartika Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the Make a Match learning model effect on students activeness in pancasila education for second grade elementary school. As well as to identify students responses to the implementation of this model. The study employed a quasi eksperimental design to measure students activeness thought tests of their pancasila education skills and student activity questionnaires. The result showed that average pretest and posttest score in the control class were 61,08 and 67,65. Respectively, while in the experimental class were 72,5 and 82,9. Based on the questionnaire, students gave an average rating 77,6% indicating that the make a match learning model was highly effective